Aberrant Oscillatory Activity during Simple Movement in Task-Specific Focal Hand Dystonia - Hinkley, Leighton B.; Dolberg, Rebecca; Honma, Susanne; Findlay, Anne; Byl, Nancy; Nagarajan, Srikantan (Frontiers in Neurology, 2012)
In task-specific focal hand dystonia (tspFHD), the temporal dynamics of cortical activity in the motor system and how these processes are related to impairments in sensory and motor function are poorly understood. Here, we use time-frequency reconstructions of magnetoencephalographic (MEG) data to elaborate the temporal and spatial characteristics of cortical activity during movement. A self-paced finger tapping task during MEG recording was performed by 11 patients with tspFHD and 11 matched healthy controls. In both groups robust changes in beta (12-30Hz) and high-gamma (65-90Hz) oscillatory activity were identified over sensory and motor cortices during button press. A significant decrease (p<0.05, 1% False Discovery Rate (FDR) corrected) in high-gamma power during movements of the affected hand was identified over ipsilateral sensorimotor cortex in the period prior to (-575ms) and following (725ms) button press. Furthermore, an increase (p<0.05, 1% FDR corrected) in beta power suppression following movement of the affected hand was identified over visual cortex in patients with tspFHD. For movements of the unaffected hand, a significant (p<0.05, 1% FDR corrected) increase in beta power suppression was identified over secondary somatosensory cortex (S2) in the period following button press in patients with tspFHD. Oscillatory activity within in the tspFHD group was however not correlated with clinical measures. Understanding these aberrant oscillatory dynamics can provide the groundwork for interventions that focus on modulating the timing of this activity.